The social structure of district school students in the Kazan governorate during the first half of the 19th century - G.V. Ibneyeva; A.I. Shakirova (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this paper, changes that took place in the social structure of district school students in the Kazan governorate during the first half of the 19th century were analyzed. It was shown that the social representation of district school students in the region under consideration changed under the influence of the government policy on education. With the help of numerous archival clerical documents, a complex study was performed to reconstruct the social image of a typical student attending any of the district schools in the Kazan governorate of that time. Based on the results of the comparative analysis of the available archival sources, a percentage ratio of students from different social classes was determined. Changes in the size of each social class were determined using mathematical methods. It was concluded that district schools of the Kazan governorate during the first half of the 19th century saw a gradual increase in the number of students representing various social classes (lower middle class, merchants, and peasants) from both urban and rural areas. At the same time, a rise in the number of students coming from the privileged social classes was also detected.